2022
DOI: 10.1021/acscatal.2c03055
|View full text |Cite
|
Sign up to set email alerts
|

Steering Carbon Hybridization State in Carbon-Based Metal-free Catalysts for Selective and Durable CO2 Electroreduction

Abstract: Electrocatalytic CO2 reduction using metal-free catalysts offers a promising and cost-effective approach to global carbon neutrality. However, metal-free catalysts frequently suffer from unsatisfactory catalytic performances, especially a low current density and poor stability. Herein, by modulating the orbital hybridization state of carbon, we strategically design a regulable sp3 and sp2 hybrid carbon interface embedded with adjacent boron and nitrogen sites in carbon-based metal-free catalysts for CO2 electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Thirdly, CO2*- ${{CO}_{2}^{^{\ast}-}}$ was protonated from HCO 3 − and adsorbed HCOO*- ${{HCOO}^{^{\ast}-}}$ was formed by obtaining second e- ${{e}^{-}}$ from the electrode. Then, formate was produced [5b,20] . To further unveil the kinetic information for the formate generation, Tafel analysis was administered in Figure 3b.…”
Section: Resultsmentioning
confidence: 99%
“…Thirdly, CO2*- ${{CO}_{2}^{^{\ast}-}}$ was protonated from HCO 3 − and adsorbed HCOO*- ${{HCOO}^{^{\ast}-}}$ was formed by obtaining second e- ${{e}^{-}}$ from the electrode. Then, formate was produced [5b,20] . To further unveil the kinetic information for the formate generation, Tafel analysis was administered in Figure 3b.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon-based, metalfree catalysts are however potential practical substitutes for noble metal-based catalysts because of good catalytic activity, selectivity and stability. [225][226][227][228][229][230] It is concluded that C 60 and derivatives are significant to development of increasingly efficient and advanced electrocatalysts and photocatalysts. This is because of electron acceptor properties, distinctive heterostructure(s) and physicochemical characteristics and electron buffers, together with high structural integrity.…”
Section: Need For Advanced Technical Supportmentioning
confidence: 99%
“…In general, the CO molecule exhibits a strong affinity to coordinate with transition metals. , If the interaction between CO and the active metal site is too strong, the CO desorption process will become difficult, thereby constraining the catalytic rate of the CO 2 RR, i.e., the poisoning effect. Attention was usually paid to enhancing the stabilization of *COOH, the key intermediate of the CO pathway, for high performance; however, this correspondingly raises the adsorption energy of the *CO intermediate, leading to a higher energy barrier of *CO desorption. Thus, how to stabilize *COOH while moderately decreasing the affinity of *CO is key and challenging to improve the electrocatalytic performance of the CO 2 RR to CO. To this end, incorporating a suitable support and tuning the electronic and geometric interactions between metal atoms and the support are an effective approach to regulate the adsorption strength and binding configuration of intermediates on the catalyst surfaces. Besides, metal atoms that have strong binding to supports could resist aggregation but may become less reactive, while weaker binding typically signifies a greater susceptibility to loss of active sites when subjected to harsh cathodic potentials. , Therefore, appropriate selection of supports and a rational understanding of the metal–support interaction are the keys to designing electrocatalysts with high catalytic performance at industrially relevant current densities for satisfying the practical application of the electrochemical CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%